Enhancing Adherence to Positive Airway Pressure Therapy for Sleep Disordered Breathing - Russell, Tonya (Seminars in Respiratory and Critical Care Medicine, 2014)
Sleep disordered breathing is made up of a group of conditions that include obstructive sleep apnea, central sleep apnea, complex sleep apnea, and sleep-related hypoventilation. Continuous positive airway pressure (CPAP) is the first-line therapy for obstructive sleep apnea. The other forms of sleep disordered breathing require different types of positive airway pressure (PAP). Adherence to PAP can be challenging and affected by multiple factors. Educating the patient regarding the consequences of untreated sleep disordered breathing and the benefits of PAP is the first step in improving adherence. Attention to social, psychological, and demographic factors that may contribute to difficulty complying is important. Addressing side effects such as nasal symptoms and equipment usability issues is also beneficial. Compliance can be monitored by the data download cards present in PAP machines, but clinicians must be aware of the limitations of the data obtained. The challenges of improving adherence occur along with the increasing need to demonstrate to payers a patient's adherence to and benefit from PAP therapy.
Keywords: positive airway pressure therapy; adherence; compliance; obstructive sleep apnea; sleep disordered breathing